Valutazioni imprenditoriali per la successione nell'impresa familiare - Riccardo, Passeri (Firenze University Press, 2008)
This book addresses the topic of entrepreneurial succession in the family business. This is a fundamental passage, frequently decisive in a type of enterprise that is extremely common in the Italian and European economic context. Consequently, it is evident that appropriate planning of this phase and a knowledge of the most pertinent strategic and operational alternatives are of crucial importance. After an initial overview of the specific features of the family business, the book addresses the typical problems related to the opening up of the corporate structure and the succession process from an entrepreneurial point of view. This is followed by an analysis of various tools for planning the succession and the principal operations deemed functional to the entrepreneurial succession process.